Social Assistance in Moroccan Courts: Criminal Cases and Alternative Sanctions as a Model - Ahmed El Amrani (Universitas Wahid Hasyim Semarang, 2026)
Under Law No. 38.15 on judicial organization, Morocco established Social Assistance Offices within the Courts of First Instance and the Courts of Appeal. This initiative aims to strengthen social assistance services within Moroccan courts, particularly by improving vulnerable groups’ access to justice and ensuring the effective realization of their constitutional rights. This article examines the institutional development of social work within Morocco’s justice sector in light of recent legislative reforms. The article also outlines the functions of social assistance within the criminal division. It further evaluates its potential contribution to implementing Law No. 44.22 on alternative sanctions, particularly for juveniles in conflict with the law, persons with disabilities, female offenders, and other vulnerable groups. أحدث المشرع المغربي بموجب القانون رقم 38.15 المتعلق بالتنظيم القضائي مكتبا للمساعدة الاجتماعية بالمحاكم الابتدائية ومحاكم الاستئناف، يرمي من ورائه إلى تثمين مكتسبات تجربة المساعدة الاجتماعية بالمحاكم المغربية في تمكين الفئات الهشة من حقها الدستوري المتمثل في الحق في التقاضي. ويسلط هذا المقال الضوء على المسار التاريخي لمأسسة مهنة المساعدة الاجتماعية بقطاع العدل بالمغرب وفق آخر المستجدات التشريعية، ويلقي نظرة مختصرة على مهامها بالقسم الزجري ليخلص إلى بيان مدى قدرتها على المساهمة الفاعلة في تنزيل مقتضيات القانون رقم 44.22 المتعلق بالعقوبات البديلة وعلى الخصوص ما تعلق بقضايا الأحداث في تماس مع القانون والأشخاص المتهمين في وضعية إعاقة والنساء الجانيات وغيرها.